MANIFESTASI KULIT PADA COVID-19 SERTA PERMASALAHAN KULIT DI ERA PANDEMI - Renata Prameswari (Oceana Biomedicina Journal, 2022)
Coronavirus disease 2019 (COVID-19) is an infection caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). This virus has affected to many countries and territories all around the world, thus in March 11, 2020 World Health Organization (WHO) declares the COVID-19 outbreak as pandemic. The symptoms of COVID-19 are varying, but most patient have mild symptom or asymptomatic. First case was describe as a ptechiae mimicking dengue fever. The most lesion are erythematous rash, followed by urticarial and varicella-like vesicle. These lesion not only caused by virus it self, however inflammatory response and drug reaction should be considered. In addition to skin manifestations in COVID-19 patients, skin problems also occur in health care workers. Health workers whom controlling COVID-19 also prone to skin and mucous membrane injury, which may caused by using Personal Protective Equipment (PPE) in long period. The purpose of this study is to describe various dermatology manifestation in COVID-19 and described various skin problem in health-care workers to controlling COVID-19 pandemic. These cutaneous manifestation combined with clinical symptoms of COVID-19 may contribute made a early diagnosis in COVID-19. Correct use of PPE can reduce skin damage in health-care workers.